Відбудова і діяльність сільських клубів Миколаївщини в повоєнний період - Ревенко, В. (Краєзнавство, 2018)
У статті на основі архівних та інших джерел досліджено складний процес відбудови сільських клубів
Миколаївщини в повоєнний період. Особлива увага зосереджена на місце і ролі клубних установ у забезпеченні дозвілля мешканців села. Визначено, що характерною рисою діяльності клубів була надмірна політизація і ідеологізація. In the article on the basis of archival and other sources, the complex process of rebuilding the village clubs of
Mykolaiv region in the post-war period was researched. Particular attention is paid to the place and role of club
institutions in providing leisure for the residents of the village. It was pointed out that clubs that had a noticeable
influence on the formation of public opinion, mood and general culture of the rural population became the main
focus of social and cultural life and communion of fellow villagers.
They did a lot of work to organize and enjoy the leisure of the peasants. Seeing in village clubs important leaders
of communist ideology, party committees of all levels kept their activities under untapped control. The main
place in the activities of village clubs was lecturing. The main task was to raise the educational, political and cultural
level of the collective farm peasantry, to educate the working people in the communist spirit, in the spirit of
the devotion of the party of Lenin - Stalin and the Soviet homeland.
The most popular and favorite, moreover, the only affordable kind of recreation among the villagers, became
cinema, amateur performances, which improved the leisure time of millions of peasants.
It is determined that the characteristic feature of the clubs was excessive politicization and ideologization.
State interference in their activities, step by step removed the clubs from the rural population.
By ignoring the cultural needs of people, the authorities turned clubs into an instrument for solving political
and agricultural tasks by way of ideological pressure on the peasants' consciousness. But despite the incredible
difficulties, rural clubs have become the main focus of social and cultural life and communication, attracting many
peasants to them, uniting them on the basis of common interests. In general, in the first post-decade decade, considerable
work was done to restore the cultural network and create the preconditions for the growth of the cultural
level of the rural population of Mykolaiv region. В статье на основе архивных и других источников исследован сложный процесс восстановления
сельских клубов Николаева в послевоенный период. Особенное внимание сосредоточено на место и роли клубных учреждений в обеспечении досуга жителей села. Определено, что характерной чертой деятельности клубов была чрезмерная политизация и идеологизация.